Strength training adaptations after cold-water immersion - Fröhlich, M.; Faude, O.; Klein, M.; Pieter, A.; Emrich, E.; Meyer, T. (The Journal of Strength and Conditioning Research, 2014)
Several studies analyzed the effectiveness of cold-water immersion (CWI) to support recovery after strenuous exercise, but the overall results seem to be conflicting. Most of these studies analyzed only short-term recovery effects, whereas the adaptational aspect has been widely neglected. Therefore, we analyzed the effects of repeated cooling after training sessions (CWI) on adaptations to strength training. Seventeen trained male students volunteered the study. After a 2-week familiarization period, a pretest (T1) of 1 repetition maximum (RM) and 12RM was conducted followed by the 5-week strength training period (within-subject design). After the posttest (T2) and a 2-week detraining period, a retention test (T3) was carried out. Directly after each training session, CWI was applied for 1 randomly assigned leg. Cooling consisted of 3 4-minute intervals with a 30-second rest period. The other leg was not cooled. A significant increase in 1RM and 12RM from baseline to T2 and T3 (p < 0.001), respectively, and a further significant increase in 12RM from T2 to T3 (p < 0.05) were observed. In addition, a tendency for a large leg effect with higher values for the "control leg" in both parameters (p = 0.08 each) and a moderate time × leg interaction in favor of the control leg was found (1RM: p = 0.11; 12RM: p = 0.09). The percentage change differences between both conditions were 1.6% for the increase in 1RM from T1 to T2 and 2.0% from T1 to T3 in favor of the control leg. Long-term strength training adaptations in trained subjects can be negatively affected by CWI. However, effects were small, and the practical relevance relative to possible recovery effects needs to be considered in a sports practical setting.